European Social Policy: Between Fragmentation and Integration - Leibfried, Stephan; Pierson, Paul (Rowman & Littlefield Publishers, 2010)
As the European Union grows and matures, its movement toward a single market has been the primary focus of attention. However, other policy areas have been greatly affected by the process of European integration. This volume deals with the development of social policy in the EU. The authors examine the substance of particular policies, such as industrial relations, immigration, agriculture, and gender equality. They emphasize the distinctive nature and dynamics of integrating policy in a "multi-tiered" systemone in which individual member states share policymaking responsibilities with central authorities. They also compare social policymaking in the EU with that in Canada and the United States, two other multi-tiered, or federal, systems. The contributors are Jeffrey J. Anderson, Brown University; Keith G. Banting, Queen's University; Patrick R. Ireland, University of Denver; Jane Lewis, London School of Economics; Ilona Ostner, Göttingen University; Martin Rhodes, University of Manchester; Elmar Rieger, University of Mannheim; George Ross, Brandeis University; Wolfgang Streeck, University of Wisconsin, Madison; and Margaret Weir, Brookings.